Enhancing Critical Thinking Skills of Junior High School Student: Development of Interactive Worksheet Based on Discovery Learning Model - Khumaeroh Dwi Nur'aini; Abdul Rachman Taufik (Jurnal Inovasi Matematika, 2025)
This study aims to develop interactive worksheet using liveworksheet based on discovery learning to improve students' critical thinking skills. This study uses the Design and Development (D&D) method and the 4D development model consisting of 4 steps, namely define, design, develop, and disseminate. However, the disseminate stage was not carried out due to time constraints in the study. The implementation of the study was carried out in class VIII MTs Almunawwaroh Merauke with a sample of 47 students. The instruments used in this study consisted of a validation sheet to test the validity of interactive worksheet, an observation sheet to test the practicality of interactive worksheet, a student response questionnaire and a test to test the effectiveness of interactive worksheet. The results of the study obtained that the interactive worksheet device that had been developed had met the criteria of valid, practical, and effective. The results of the validity of interactive worksheet by experts obtained an average value of the validation results in each aspect in the valid category. The results of the practicality of interactive worksheet obtained an average value in the aspect in the practical category. The results of the effectiveness of the interactive worksheet were obtained from the results of student responses and the improvement of students' critical thinking skills. The results of the student responses obtained positive responses and students' critical thinking skills of 0.665 with a moderate category with an interpretation of effectiveness in the effective category. These results indicate that the use of the interactive worksheet that has been developed is an alternative to improve students' critical thinking skills.